2018
DOI: 10.14744/anatoljcardiol.2018.59932
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angiography using the left distal radial approach - An alternative site to conventional radial coronary angiography

Abstract: Objective:To share our experience with the left distal radial approach for transradial coronary angiography and interventions. By performing the radial puncture in the fossa radialis or the so called anatomical “Snuffbox” we aimed to present the feasibility and complications of this new technique.Methods:Left distal radial artery was used as an access site in 54 patients admitted to our clinic for coronary angiography and intervention between May 25th and October 20th 2017. All of them had pulse in their left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
78
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 15 publications
6
78
1
6
Order By: Relevance
“…PCI cases inevitably had longer hemostasis time due to higher dose of heparin; however, our study interestingly showed that PCI case with distal TRA had similar hemostasis time compared to diagnostic catheterization with conventional TRA. Early hemostasis control has been reported from prior studies to be within 3 hr . Smaller vessel size distal to the bifurcation, superficial position, and anatomical position over a bony basement are plausible explanations for this finding.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…PCI cases inevitably had longer hemostasis time due to higher dose of heparin; however, our study interestingly showed that PCI case with distal TRA had similar hemostasis time compared to diagnostic catheterization with conventional TRA. Early hemostasis control has been reported from prior studies to be within 3 hr . Smaller vessel size distal to the bifurcation, superficial position, and anatomical position over a bony basement are plausible explanations for this finding.…”
Section: Discussionmentioning
confidence: 64%
“…Early hemostasis control has been reported from prior studies to be within 3 hr. 9,12 Smaller vessel size distal to the bifurcation, superficial position, and anatomical position over a bony basement are plausible explanations for this finding. Faster hemostasis without increased risk of complication is clinically meaningful in terms of post-procedural care as well as patient comfort, and also economically meaningful as the same-day discharge is shown to offer substantial cost savings.…”
Section: Discussionmentioning
confidence: 93%
“…In another prospective observational study by Roghani‐Dehkordi et al, 216 patients (radial 111 and ulnar 105) underwent catheterization and PCI with more radial artery occlusion (9% vs. 1%, p < .05) and radial spasm compared with ulnar catheterization (12.6 vs. 1.9%, p < .05). A prospective Turkish study of 54 patients showed that DDRA cardiac catheterization and PCI was safe . A recent randomized Greek study of 200 patients who underwent radial versus DDRA coronary angiography ( n = 100, each group) by experienced operators showed lower rates of successful access and manual hemostasis time in the DDRA cohort ( p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Distal radial "snuffbox" approach has recently been reported mainly in the fields of the coronary artery 1,3,4) and abdominal lesions, 5,6) but this is the initial report for neuroendovascular treatment. The present case was an unruptured dissecting aneurysm of the left vertebral artery with very wide neck, hence stent-assisted technique was necessary to coil embolization.…”
mentioning
confidence: 98%
“…First, puncture is more difficult than that through the conventional radial approach because of smaller diameter of the vessel. In studies reported by researchers of the coronary interventions, 1,3,4) the indication of this method was limited to cases with the presence of a palpable artery in the anatomical snuffbox, and cases with weak or absent pulse were excluded. When cases with favorable pulsation were selected, a technical success rate of 88%-100% was achieved.…”
mentioning
confidence: 99%